2016
DOI: 10.1111/pere.12118
|View full text |Cite
|
Sign up to set email alerts
|

Men's sociosexuality is sensitive to changes in mate availability

Abstract: Correlational research has linked mate availability to human sexual behavior, whereby unrestricted sociosexuality seems to be most common under conditions of female abundance. In this study, 71 heterosexual men were randomly assigned to one of two mate availability priming conditions, mate scarcity or mate abundance, and subsequently completed measures of sociosexuality as well as infidelity intentions. Results indicated that men in the mate abundance condition reported stronger sociosexual attitudes and desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Attitude toward sexual strategies was manipulated using a fictitious magazine article about low mate availability (adapted from Spielmann et al, 2009). Arnocky et al (2016) found that this manipulation affected sociosexual attitudes (with stronger effects for men), such that those in the low mate availability condition more strongly endorsed monogamy than those in the high mate availability condition. All study materials are available at https://osf.io/bfgmk/.…”
Section: Manipulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attitude toward sexual strategies was manipulated using a fictitious magazine article about low mate availability (adapted from Spielmann et al, 2009). Arnocky et al (2016) found that this manipulation affected sociosexual attitudes (with stronger effects for men), such that those in the low mate availability condition more strongly endorsed monogamy than those in the high mate availability condition. All study materials are available at https://osf.io/bfgmk/.…”
Section: Manipulationsmentioning
confidence: 99%
“…Two studies were conducted, one with a college student sample and one with an online community sample, to assess replicability and generalization of findings. For each study, participants were randomly assigned to a pathogen threat (White et al, 2013), low mate availability (Arnocky et al, 2016), or control condition. Political ideology, attitudes toward sexual strategies, and disgust were assessed.…”
Section: Present Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectrum of sociosexuality provides plurality in mating tactics, which can be adaptive in different contexts (Gangestad & Simpson, 2000). For example, in a context where sharing of resources and parental investment is needed, people can be inclined to be more restrictive in sociosexuality (Conroy-Beam et al, 2015), whereas in a context where accessibility to mates is low, people can be inclined to be more unrestricted in sociosexuality (Arnocky et al, 2016).…”
mentioning
confidence: 99%